2020
DOI: 10.3389/fphys.2020.616167
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Simple Renal Cysts and Renal Function in Patients With Type 2 Diabetes

Abstract: Introduction: Simple renal cysts (SRCs) are the most common acquired cystic kidney disease, but the relationship between SRCs and renal function has not been clarified in patients with type 2 diabetes mellitus (T2DM).Methods: A retrospective study was conducted to analyze the clinical features of renal cysts and ultrasound data of the kidney in 4,304 patients with T2DM.Results: The prevalence of SRCs in patients with T2DM was 21.1%. Compared to patients with no SRCs, patients with SRCs had worse renal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“… 19 , 38 , 39 In a recent study, SRCs were associated with worse renal function in patients with T2D, age, gout, proteinuria, cerebrovascular disease (CVD), and increased serum phosphorus levels. 15 Consistently, another study demonstrated that hyperuricemia was the critical risk factor for SRCs in T2D. 28 In our study, we also observed a decreased iGFR and eGFR in T2D patients with SRCs, but our analyses showed that the volume of SRCs was not associated with the eGFR or iGFR level, and it did not significantly affect the split kidney function.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… 19 , 38 , 39 In a recent study, SRCs were associated with worse renal function in patients with T2D, age, gout, proteinuria, cerebrovascular disease (CVD), and increased serum phosphorus levels. 15 Consistently, another study demonstrated that hyperuricemia was the critical risk factor for SRCs in T2D. 28 In our study, we also observed a decreased iGFR and eGFR in T2D patients with SRCs, but our analyses showed that the volume of SRCs was not associated with the eGFR or iGFR level, and it did not significantly affect the split kidney function.…”
Section: Discussionsupporting
confidence: 87%
“…Thereafter, we evaluated the general characteristics and kidney function between these two groups and observed significant differences in the BMI, eGFR, and iGFR, consistent with the literature. 15 , 18 , 19 This higher BMI in T2D with cysts could be attributed to insulin resistance, hypertension, hyperuricemia induced by adipose tissue inflammation or oxidative stress, as previously reviewed in multiple studies. 20 A previous study reported that obesity prevalence is significantly higher in patients with renal cysts than in those without.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to investigate the association of SRCs and its characteristics with metabolic syndrome with adjustments for many important cardio-metabolic variables in a relatively large population. Although the mechanism underlying the link between SRCs and metabolic syndrome is still unclear, recent studies showed that SRCs were found to be associated with an increased risk of albuminuria in young adults ( 24 ) and SRCs are also associated with worse renal function in type 2 diabetes patients ( 25 ). The negative impact of SRCs in general population of this study was similar to young adults and diabetes patients in the two studies mentioned above ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying the link between SRCs and metabolic syndrome is still unclear, recent studies showed that SRCs were found to be associated with an increased risk of albuminuria in young adults ( 24 ) and SRCs are also associated with worse renal function in type 2 diabetes patients ( 25 ). The negative impact of SRCs in general population of this study was similar to young adults and diabetes patients in the two studies mentioned above ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%